SUBJECTS OF COLLECTIVE LABOR DISPUTES - Nurullaeva , Oydin (Educational Research in Universal Sciences, 2023)
The subject of a collective labor dispute are employees (their representatives) on the one hand and employers (their representatives) on the other. At the local level, the subject of a collective labor dispute may be employees of the organization, branch, representative office, other separate structural subdivision. Workers united to certain groups according to other criteria (shift workers, workshops, a certain profession, trade union members), cannot be subject to collective labor dispute.